The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s12633-021-01554-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variations in Microwave Processing Temperatures on Microstructural and Mechanical Properties of AA7075/SiC/Graphite Hybrid Composite Fabricated by Powder Metallurgy Techniques

Abstract: Due to the demand in present industrial, aerospace, defense sectors for lightweight high-performance aluminum (Al) particle-reinforced metal matrix composites, the advancement of techniques to fabricate these composites with superior mechanical properties have gained technological interest in the modern world. In this direction, SiC and graphite reinforced AA7075 matrix composite material has been fabricated in this study, through hybrid microwave sintering techniques. The microwave sintering temperatures for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…38 To eradicate this agglomeration formation and to improve mechanical properties researchers generally employed the microwave sintering technique to synthesize HMMC. 21 As ceramic reinforcements are excellent microwave absorbers, adding hard ceramic particles such as SiC or Snail shell powder with large microwave penetration depths and low loss tangent values helps achieve higher mechanical properties with fewer flaws. 19,22 The U.T.S and compression strength values for the microwave-sintered A6Si6SS HMMC at different sintering temperatures was shown in Figure 13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 To eradicate this agglomeration formation and to improve mechanical properties researchers generally employed the microwave sintering technique to synthesize HMMC. 21 As ceramic reinforcements are excellent microwave absorbers, adding hard ceramic particles such as SiC or Snail shell powder with large microwave penetration depths and low loss tangent values helps achieve higher mechanical properties with fewer flaws. 19,22 The U.T.S and compression strength values for the microwave-sintered A6Si6SS HMMC at different sintering temperatures was shown in Figure 13.…”
Section: Resultsmentioning
confidence: 99%
“…The green compacts were subjected to conventional sintering at 600°C for 2 h and MAS at 400 °C, 450 °C, 500 °C and 550 °C for 30 min at a 10°C/min heating rate. 21 Composites were preheated using a SiC susceptor until they reached critical temperatures for internal heat generation during the absorption of the microwaves. 22,23 Initially, the Al- x% SiC ( x = 2 wt%, 4 wt%, 6 wt%, 8 wt%, 10 wt%) composites were made through powder metallurgy technique.…”
Section: Materials and Fabrication Methodsmentioning
confidence: 99%
“…the dielectric properties of the as-received aluminium and kaolin powders were measured by using the network analyzer operating at a frequency of 0.5-3 Ghz integrated with a dielectric kit probe [19]. tensile and compression tests were performed as per aStm e8 and aStm e9 standards on the m30 model micro universal testing machine [20]. the eConomet Vh1md micro Vickers hardness tester was utilised to assess the hardness of the composite as per aStm e384-16 specifications with the application of a 500 g load [21].…”
Section: Composite Characterization Methodsmentioning
confidence: 99%
“…Strong interface bonds are responsible for effective load transfer mechanisms from matrix to reinforcements. According to some studies on Al-B 4 C interface chemistry, effective load transfer mechanisms have been observed in the case of partially reacted interfaces [37,38]. From the studies of chemical reactivity between Al-B 4 C systems, it is concluded that partial chemical reactions at interface regions lead to the formation of an interface that is more than a physical bond and less than a fully reacted interface region [17].…”
Section: Mechanical Propertiesmentioning
confidence: 99%